Exploration of Differences In Students Creative Thinking Abilities Viewed from Perspective Gender and Domicile: Rasch Model Analysis - syafrial syafrial; Abdul Kadir; Zainuddin (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The purpose of this study was to explore differences in students creative thinking abilities based on gender and domicile. The research method used was descriptive quantitative. Sampling used proportional random sampling technique at Public Junior High Schools in South Konawe Regency. The research instrument used a creative thinking test as primary data. The data analysis technique used the winsteps program with scalogram analysis. The results showed that female students tended to be superior in fluency, originality, and elaboration, both at very high and low levels of creative thinking ability, while male students showed superiority in flexibility. This difference can be influenced by biological, psychological, and social factors that play a role in cognitive development and creativity. In addition, differences in creative thinking abilities were also found based on domicile. Urban students are superior in several indicators at very high levels of creative thinking ability, but are more susceptible to decreased creativity at very low levels compared to rural students. Environmental factors such as access to educational resources, intellectual stimulation, and higher social support in urban areas play a role in this difference. Overall, these findings confirm that gender and domicile significantly influence students creative thinking abilities.